Global planning innovations for urban sustainability - Darche, Sebastien; Searle, Glen (Routledge, 2019)
"As the world becomes more urbanised, solutions are required to solve current challenges for three arenas of sustainability: social sustainability, environmental sustainability and urban economic sustainability. This edited volume interrogates the trade-offs made between the three arenas of sustainability in the implementation of innovative solutions in cities, and in doing so offers a new perspective on the politics of urban planning innovation and urban sustainability. The book draws on a group of 12 international case studies, including Vancouver and Calgary in Canada, San Francisco and Los Angeles in the U.S (North America), Yogyakarta in Indonesia, Seoul in Korea (South-East Asia), Medellin in Colombia (South America), Helsinki in Finland, Freiburg in Germany and Seville in Spain (Europe). Each case study provides key facts about the city, presents the particular urban sustainability challenge and the planning innovation process and examines the trade-offs between social, environmental and economic sustainability. The book analyses to what extent planning innovations can be translated from one context to another, referred to as the transferability of innovations." -- Provided by publisher.